Assessing the dpsa’s, and partners’, perspectives on digitalisation for improving efficiencies in the south african public sector - Lukhele, Nompumelelo (University of the Witswatersrand, Johannesburg, 2023)
The purpose of this research was to explore the perspectives of public sector officials placed in the e-Government Services and Information Management unit of the DPSA, and partners, who are responsible for coordinating and drafting the Digital Government Policy Framework, on the implementation of digitalisation in the context of improving public sector efficiencies. This was justified as important because, the attitudes and perceptions of policy developers about digitalisation will influence the directionality of policies they develop on the implementation of digitalisation or the digital transformation agenda more broadly. The research primarily questioned what the perspectives of these officials are on the implementation of digitalisation in the context of improving public sector efficiencies in South Africa. The study adopted qualitative research methods. Semi-structured interviews and case studies were adopted to respond to the research questions. The main findings were that there is a need for government to strengthen the legitimacy of government digital transformation through releasing decisive political will; there is a need for elevation of the position of the Chief Information Officer in government departments; and lastly there is a need for the establishment of a central agency that will guide transformation of public service administration to perform important functions required to successfully transition to a digital government. The study concludes by emphasising the risks at local, regional, and international levels that the South African government faces if the urgency to act is undermined
A research report submitted to the Faculty of Management, University of the Witwatersrand, in 50% requirement of the requirements for the degree of Master of Management (in the field of governance and public policy)
Keywords: DPSA’S; UCTD; Digitalisation; Public Sector; South Africa; Information Management unit; e-Government Services; SDG-9: Industry, innovation and infrastructure